How Web Shops Impact Consumer Behavior? - Štimac, Helena (Array, 2021)
The behavior of e-customers is quite unpredictable, which raises additional questions about this topic. The purpose of the paper is to conduct research on e-customers, understand the impact of marketing actions on e-customer behavior and understand the unpredictability of e-customers. Research was conducted on the Mlinar web shop that sells cakes. 284 respondents/buyers had the opportunity to solve questionnaires about behavior after purchase and consumption of product. Different methods have been used in the analysis - descriptive statistics, multivariate analysis (reliability analysis, correlation analysis and linear regression) and analysis of variance (ANOVA). The results showed that most examinees were satisfied with online shopping on the Mlinar web shop and that they are impulsive when online shopping. Saving time is the main reason to buy on a web shop. Research proved that variables such as firm reputation/perceived value, e-satisfaction and online services positively affect the creation of e-loyalty in their users.